STUDI TENTANG PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DAN MADRASAH - Efendi, Asip; Pahrudin, Agus; Jatmiko, Agus; Koderi (re-JIEM (Research Journal of Islamic Education Management), 2024)
Developing the Islamic Religious Education curriculum in Indonesia is very important and urgent due to changing social, cultural, and technological dynamics. This study aims to analyze the development of the Islamic Religious Education curriculum in schools and madrasahs in Indonesia, which is increasingly important given social, cultural, and technological changes that affect the needs of learners. This research is expected to provide practical recommendations for improving the quality of religious education through a relevant and effective curriculum. The research method used is a descriptive qualitative approach, with data collected through observation, in-depth interviews, and document analysis, such as syllabi and lesson plans. Data analysis was conducted using an interactive method to find the main themes in implementing the Islamic Religious Education curriculum. The results show that most teachers still need the training to understand the "Merdeka Curriculum". At the same time, the availability of infrastructure and the use of modern technology media such as gamification greatly affect the quality of learning. The findings offer valuable insights for policymakers and educators in designing an Islamic Religious Education curriculum that better addresses contemporary educational needs.